Hubungan Beban Kerja Dengan Stres Kerja Pada Karyawan PT. Kemuning Group Medan - Delorenzo Purba, Diatei Yozeff; Chandra, Andy (Universitas Medan Area, 2025)
This study aims to analyze the relationship between workload and work stress in employees of PT. Kemuning Group Medan. The background of the research is based on the phenomenon of increasing demands on company productivity which is often not proportional to the physical and psychological capacity of employees, thus giving rise to symptoms of work stress. The study used a quantitative approach with a correlational method and involved the entire active employee population of 93 people through a total sampling technique. Data was obtained using a four-level Likert scale-based questionnaire that had been tested for validity and reliability, then analyzed by Pearson's Product Moment correlation test through the SPSS program. The results of the descriptive analysis show that the level of workload and work stress of employees is in the high category. Furthermore, the correlation test showed a significant positive relationship with the value of Rxy = 0.809 (p 0.05), where workload contributed 65.4% to work stress. These findings confirm that overload is the dominant factor affecting employee work stress. Practically, the results of the study recommend the need for workload management, stress intervention programs, and social support in the work environment to maintain employee well-being and productivity.